STARTeCH for asynchronous interactive grammar learning: Transforming ESL mastery in Malaysian schools - Siti Shuhaida Shukor; Qiu Chuane; Intan Safinas Mohd Ariff Albakri; Noor Alhusna Madzlan; Revathi Gopal (Studies in English Language and Education, 2025)
The post-pandemic emphasis on educational experimentation underscores STARTeCHs call for swift school reform and the transformative potential of extracurricular learning. This study investigates the impact of STARTeCH on ESL grammar test scores on ESL grammar scores using online learning modes. Utilizing a quasi-experimental design, 87 Malaysian lower secondary school learners (43 males, 44 females, average age 13), selected via purposive sampling, were divided into asynchronous group (n=29), synchronous group (n=30), and conventional group (n=28). Instruments included pre- and post-tests and CAP (Cognitive, Affective, Psychomotor) questionnaires. ANOVA results indicated significant post-intervention differences among the groups F(2.84)=7.834, p=0.001), with the asynchronous group notably outperforming both synchronous and conventional groups in grammar test scores. The study further uncovered no significant differences in cognitive and affective perceptions between asynchronous and synchronous as well as conventional groups. Furthermore, the study revealed a strong preference for the asynchronous mode, particularly in enhancing psychomotor learning objectives. STARTeCH is found to be efficient in enhancing ESL grammar proficiency through tailored, flexible online learning environments with room to practice, repetition, and hands-on engagement via the asynchronous mode. The study suggests a reconsideration of traditional methods, advocating for flexible, technology-enhanced pedagogies for educators, curriculum developers, and policymakers within ESL education.